2013
DOI: 10.1002/rrq.53
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Reading Disability Risk and Environmental Protective Factors in Students' Reading Fluency in Grade 4

Abstract: This study examined the role of reading disability (RD) risk and environmental protective factors in reading fluency in grade 4. The sample consisted of 538 Finnish‐speaking students. Kindergarten measures included the students' risk for RD based on poor achievement in phonological awareness and letter knowledge as well as information on the three control variables: nonverbal ability, level of parental education, and gender. Measures in grades 1–3 included environmental protective factors: classmate reports of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 144 publications
(194 reference statements)
1
22
0
1
Order By: Relevance
“…Furthermore, some evidence suggests that high levels of ST that result in low energy expenditure may impair learning by decreasing plasma levels of brain-derived neurotrophic factor 2 . PA and ST likely have similar effects on the brain in girls and in boys, but other factors, such as parental educational support, peer acceptance, teachers’ positive attitude for the student, and children’s motivation towards school are more important correlates of academic achievement than PA and ST among girls [32], [33]…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, some evidence suggests that high levels of ST that result in low energy expenditure may impair learning by decreasing plasma levels of brain-derived neurotrophic factor 2 . PA and ST likely have similar effects on the brain in girls and in boys, but other factors, such as parental educational support, peer acceptance, teachers’ positive attitude for the student, and children’s motivation towards school are more important correlates of academic achievement than PA and ST among girls [32], [33]…”
Section: Discussionmentioning
confidence: 99%
“…Externalizing problems was measured with 10 items, five measuring conduct problemsfor example, "Generally obedient" (reversed) and "Often fights with other children or bullies them"-and five measuring hyperactivity/ inattention-for example, "Restless, overactive, cannot stay still for long" and "Thinks things out before acting Positive teacher affect in Grade 1. The teachers rated their positive affect for each target student in Grade 1 on a 5-point scale (from 1 not at all to 5 very often) (see also Kiuru et al, 2013Kiuru et al, , 2014. Positive teacher affect was measured with two items ("When you teach this child how often do you feel satisfied" and "When you teach this child how often do you feel joy"; Cronbach's .90).…”
Section: Methodsmentioning
confidence: 99%
“…For example, a study of children with RD showed that the effect of RD on reading fluency was mediated by support from teachers and peers with a cumulative effect [47] – the contribution of interpersonal protective factors will be discussed more in the section on socio-emotional resilience.…”
Section: Cognitive Resiliencementioning
confidence: 99%